The Association of Phosphodiesterase 5 Inhibitor on Ischemia-Reperfusion Induced Kidney Injury in Rats - Nam, Jong Kil; Kim, Jung Hee; Park, Sung Woo; Chung, Moon Kee (Urology Journal, 2020)
Purpose: Ischemia-reperfusion (IR) causes various damage in renal tissues. The aim of the present study was to evaluate the renoprotective effect of phosphodiesterase 5 inhibitor (PDE5I) on IR induced renal injury in a rat model. Materials and Methods: Thirty adult male, 12-week-old, Sprague-Dawley rats were divided into three groups. Renal IR injury was induced by occlusion of the bilateral renal pedicle for 45 min followed by reperfusion for 24 h. The rats were sacrificed for collecting blood and tissue specimens. IR rats were administered daily oral Tadalafil (group I) or no pills (group II), while sham-operated animals were treated with no pills (sham group). The pill was diluted with distilled water and administered to rats for 15 days, orally. Renal histopathology, function, pro-inflammatory and inflammatory cytokines and mediators were assessed by serum creatinine, western blot assay and immunohistochemistry. Results: Compared with sham group, rats that underwent renal IR operation exhibited a significant increase in concentration in serum creatinine (p< .01) and tissue pro-inflammatory and inflammatory mediators. In group I, however, tadalafil significantly suppressed elevation of the serum creatinine and increased the levels of endothelial nitric oxide synthase and decreased the level of intercellular adhesion molecule-1 (ICAM-1) than group II (p< .05). Moreover, tadalafil prevented IR-induced expression of pro-inflammatory mediators such as monocyte chemotactic protein-1 (MCP-1) (p< .05). Conclusion: Tadalafil significantly promotes functional recovery after renal IR injury and effectively inhibits the induction of pro-inflammatory and inflammatory mediators. The results substantiate Tadalafil as a protective agent against IR-induced renal injury.